A theory of social comparison processes - Festinger,Leon
In this paper we shall present a further development of a previously published theory concerning opinion influence processes in social groups (7). This further development has enabled us to extend the theory to deal with other areas, in addition to opinion formation, in which social comparisons is important. Specifically, we shall develop below how the theory applies to the appraisal and evaluation of abilities as well as opinions.Such theories and hypotheses in the area of social psychology are frequently viewed in terms of how "plausible" seem. "Plausibility" usually means whether or not the theory or hypothesis fits one's intuition or one's common sense. In this meaning much of the theory or hypothesis fits one's intuition or one's common sense. In this meaning much of the theory which is to be presented here is not "plausible". The theory does, however, explain a considerable amount of data and leads to testable derivations. Three experiments, specifically designed to test predictions from this extension of the theory, have now been completed (5,12,19). They all provide good corroboration. We will in the following pages develop the theory and the present the relevant data.